K-12 ESL Writing Instruction: A Review of Research on Pedagogical Challenges and Strategies - Bhowmik, Subrata; Kim, Marcia (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2021)
Writing is an important early literacy skill for English as a Second Language (ESL) students’ academic success, underlining the importance of effective ESL writing instruction at the K-12 level. However, there is little empirical research on ESL writing instruction in school settings. The goal of this systematic literature review is to examine the extant empirical evidence of the challenges teachers encounter in teaching ESL writing and the strategies that can be adopted to help teachers overcome the challenges. Our search yielded 49 peer-reviewed journal articles and book chapters published between 2010-2019. A content analysis (Stan, 2009) of these materials indicated that teachers encounter the following challenges in teaching K-12 ESL writing: (a) lack of pre-service training in ESL writing, (b) lack of writing pedagogy skills, (c) lack of time, (d) lack of professional development opportunities, (e) standardized tests, and (f) unique L1 influences on L2 students’ text production. The content analysis also revealed the following strategies that can be recommended for addressing these challenges: (a) incorporating an ESL writing course into teacher education programs, (b) creating opportunities for writing pedagogy support by mentor teachers and researchers, (c) incorporating integrated skills development in the writing classroom, (d) providing students with opportunities to write more, (e) adopting explicit writing instruction, and (f) creating professional development opportunities for teachers. Based on our findings, we discuss implications and recommendations for ESL writing instruction in K-12 schools.